Pink 2.0 : encoding queer cinema on the internet - Tsika, Noah, 1983- (Indiana University Press, 2016)
In an era where digital media converges with new technologies that allow for cropping, remixing, extracting, and pirating, a second life for traditional media appears via the internet and emerging platforms. Pink 2.0 examines the mechanisms through which the internet and associated technologies both produce and limit the intelligibility of contemporary queer cinema. Challenging conventional conceptions of the internet as an exceptionally queer medium, Noah A. Tsika explores the constraints that publishers, advertisers, and content farms place on queer cinema as a category of production, distribution, and reception. He shows how the commercial internet is increasingly characterized by the algorithmic reduction of diverse queer films to the dimensions of a highly valued white, middle-class gay masculinity'a phenomenon that he terms "Pink 2.0." Excavating a rich set of online materials through the practice of media archaeology, he demonstrates how the internet's early and intense associations with gay male consumers (and vice versa) have not only survived the medium's dramatic global expansion but have also shaped a series of strategies for producing and consuming queer cinema. Identifying alternatives to such corporate and technological constraints, Tsika uncovers the vibrant lives of queer cinema in the complex, contentious, and libidinous pockets of the internet where resistant forms of queer fandom thrive.